MALIGNANT STRUMA OVARII (KASUS LANGKA) - Adi Arianto; Udadi Sadhana (Universitas Batam, 2023)
Struma ovarii (SO) are rare and accur in 2-3% of mature ovarian teratomas, most SO cases are benign. Malignant struma ovarii (MSO) is even more rare and occurs in 0,5- 5% of all cases, with the most common histologies identified are papillary and follicular carcinoma, most commonly affect patients in their 4th to 6th decade of life. Due to the rarity of malignant transformation, data about its management are lacking. A 49-years-old woman P2A0 with abdominal pain and pelvic mass, admitted for a hysterectomy and bilateral salpingo-oophorectomy. The left ovary was measured 13x11x5 cm, cystic and partly solid, filled with gelatinous fluid, composed of thyroid follicles with the appearance of